Brake disc, preparation method, braking system and vehicle

By introducing nanoporous zones into the dense zone of the carbon ceramic brake disc, the combined structure of cracked carbon and carbon particles is used to solve the crack problem caused by the brittleness of the carbon ceramic brake disc, and its toughness and service life are significantly improved.

CN119504276APending Publication Date: 2025-02-25BYD CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311088529.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The carbon ceramic brake disc is prone to cracks due to its brittle material composition, resulting in a short service life, which seriously restricts its application.

Method used

A number of nanoporous regions are distributed between the dense regions of the brake disc. The nanoporous regions are composed of cracked carbon in a continuous phase and carbon particles dispersed therein, with a pore size of 10 nm to 100 nm and a porosity of 15% to 30%.

Benefits of technology

Through the energy absorption effect of the nanoporous zone, crack expansion and diffusion are reduced, and the toughness and service life of the brake disc are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504276A_ABST
    Figure CN119504276A_ABST
Patent Text Reader

Abstract

The invention provides a brake disc, a preparation method, a braking system and a vehicle. The brake disc comprises a compact area and a plurality of nano-porous areas distributed in the compact area at intervals. Wherein the compact area comprises a carbon fiber reinforced silicon carbide material, and the nano-porous area comprises continuous-phase cracked carbon and carbon particles distributed in the cracked carbon; wherein the pore diameter of the nano-porous area is in the range of 10 nm to 100 nm, and the porosity is in the range of 15% to 30%. The nano porous area in the brake disc can improve the toughness of the brake disc, so that the service life of the carbon ceramic brake disc can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of brake materials, and in particular to brake discs and preparation methods, brake systems and vehicles. Background Art

[0002] Carbon ceramic brake discs are gradually gaining popularity in the market due to their superior performance. The material of carbon ceramic brake discs generally includes carbon fiber reinforced silicon carbide / silicon, where carbon fiber provides toughness and silicon carbide provides wear resistance. The continuous phase composed of two brittle materials, silicon carbide and free silicon, makes the continuous phase prone to cracks when subjected to external forces. The cracks will also extend to the interface between the carbon fiber and the continuous phase material, resulting in longer cracks in the final brake disc; under long-term alternating loads, the brake disc will form through cracks, causing the brake disc to break, which seriously restricts the service life of the carbon ceramic brake disc. Summary of the invention

[0003] In view of this, the present application provides a brake disc, in which the nanoporous area can improve the toughness of the brake disc, thereby extending the service life of the carbon-ceramic brake disc.

[0004] In a first aspect, the present application provides a brake disc, comprising a dense region and a plurality of nanoporous regions spaced apart and distributed in the dense region;

[0005] The dense region comprises carbon fiber reinforced silicon carbide material, and the nanoporous region comprises cracked carbon in a continuous phase and carbon particles distributed in the cracked carbon; the pore size of the nanopores in the nanoporous region is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%.

[0006] The nanoporous structure in the nanoporous area makes the nanoporous area looser than the dense area on the nanoscale, and the interfacial bonding force between the cracked carbon and the carbon particles is weak. When the brake disc is subjected to external force and cracks appear in the dense area, the cracks extend to the nanoporous area and along the interface of the cracked carbon / carbon particles in the nanoporous area. This extension process is also the energy absorption process of the cracks, so the cracks will gradually disappear. Therefore, the toughness of the brake disc can be significantly improved and the service life of the brake disc can be extended.

[0007] Optionally, the size of the nanoporous region is in the range of 30 μm to 500 μm.

[0008] Optionally, based on the volume of the brake disc, the sum of the volume percentages of the plurality of nanoporous regions is in the range of 5% to 30%.

[0009] Optionally, based on the total mass of the nanoporous region, the nanoporous region includes 30% to 70% of the carbon particles, 10% to 40% of the cracked carbon, and 0% to 50% of the silicon carbide particles.

[0010] Optionally, in the nanoporous region, the mass percentage of the silicon carbide particles is 5% to 50%.

[0011] Optionally, the carbon particles have a particle size of 0.1 μm to 10 μm.

[0012] Optionally, the D50 particle size of the silicon carbide particles is 0.3 μm to 20 μm.

[0013] A second aspect of the present application provides a method for preparing a brake disc, comprising the following steps:

[0014] (1) immersing a carbon fiber tow into a solution of a first resin, taking it out, drying, curing, and shearing it to obtain a carbon fiber reinforced resin strip;

[0015] (2) heating and pressurizing a first raw material including carbon particles and a second resin powder in a mold to solidify the first raw material, and then crushing and sieving the first raw material to obtain a granular second raw material;

[0016] (3) mixing the carbon fiber reinforced resin strip, the second raw material, the third resin powder and the solvent, heating and stirring until the solvent evaporates to obtain a mixture; crushing and sieving the mixture, transferring it to a mold for heating and pressurizing to cure, and obtaining a brake disc blank; wherein the brake disc blank comprises a first material distribution area and a plurality of second material distribution areas dispersed in the first material distribution area, the first material distribution area comprising the carbon fiber reinforced resin strip and the third resin powder; the second material distribution area comprising the second raw material and the third resin powder;

[0017] (4) performing a carbonization treatment on the brake disc blank under a protective atmosphere, and then performing a siliconizing treatment to obtain a brake disc;

[0018] The brake disc includes a dense area and a plurality of nanoporous areas spaced apart in the dense area; the dense area includes carbon fiber reinforced silicon carbide material, and the nanoporous area includes cracked carbon in a continuous phase and the carbon particles dispersed in the cracked carbon; the pore size of the nanoporous area is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%. The preparation method has simple steps, strong process reliability, high production efficiency, and can realize large-scale industrial production.

[0019] Optionally, based on the total mass of the mixture, the mixture includes 20% to 50% of the carbon fiber reinforced resin strips, 20% to 40% of the second raw material and 20% to 40% of the third resin powder.

[0020] Optionally, the length of the carbon fiber reinforced resin strip is 0.5 cm to 3 cm.

[0021] Optionally, based on the total mass of the first raw material, the first raw material includes 30% to 60% of the carbon particles, 20% to 50% of the second resin powder and 0% to 40% of the silicon carbide particles.

[0022] Optionally, in step (2), the screening is performed using a sieve with a mesh size of 50 to 400.

[0023] Optionally, in step (3), the screening is performed using a sieve with a mesh size of 15 to 30.

[0024] The third aspect of the present application provides a braking system, including the brake disc provided by the first aspect of the present application. Due to the use of the carbon-ceramic brake disc provided by the first aspect of the present application, the braking system has a better braking effect, higher reliability, and longer service life.

[0025] Optionally, the braking system includes the carbon-ceramic brake disc, a brake caliper bracket, a brake caliper housing and a friction plate.

[0026] The fourth aspect of the present application provides a vehicle, comprising the braking system provided by the third aspect of the present application. Due to the braking system provided by the third aspect of the present application, the vehicle has good market competitiveness.

[0027] Optionally, the transportation vehicle includes a vehicle or an airplane; wherein the vehicle includes a car or a train for rail transit. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a simplified schematic diagram of the structure of any area on any cross section of the brake disc provided in an embodiment of the present application.

[0029] Figure 2 This is a scanning electron microscope (SEM) photograph of the cross section of the brake disc prepared in Example 2 of the present application.

[0030] Explanation of reference numerals: 1-brake disc; 10-dense area; 20-nanoporous area. DETAILED DESCRIPTION

[0031] Generally, carbon ceramic brake discs are directly obtained by siliconizing carbon fiber / carbon porous carbon. The obtained carbon ceramic brake discs are all nano-dense structures, which are relatively brittle and lack toughness. After long-term use, through cracks are easy to appear, causing the carbon ceramic brake disc to break, seriously affecting the service life of the carbon ceramic brake disc. In order to solve the above technical problems, the embodiment of the present application provides a brake disc, see Figure 1 The brake disc 1 includes a dense region 10 and a plurality of nanoporous regions 20 spaced apart in the dense region 10; specifically, in some embodiments, the nanoporous region 20 is surrounded by the dense region 10;

[0032] The dense region 10 includes carbon fiber reinforced silicon carbide material, and the nanoporous region 20 includes cracked carbon in a continuous phase and carbon particles distributed in the cracked carbon; the pore size of the nanoporous region 20 is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%. Specifically, the dense region 10 includes a continuous phase of silicon carbide material and carbon fiber reinforcement distributed in the continuous phase; the pore size refers to the pore size of nanopores in the nanoporous region 20.

[0033] The carbon fiber in the dense area can provide a certain toughness for the brake disc, but based on the use characteristics of the brake disc, a large amount of silicon carbide is required as a continuous phase in the dense area, which makes the dense area of ​​the brake disc still dominated by brittleness and insufficient toughness. The nanoporous structure in the nanoporous area dispersed in the dense area makes the nanoporous area looser at the nanoscale relative to the dense area. Because the materials of the nanoporous area are mainly cracked carbon and carbon particles, the interface bonding force between the two materials is weak. When the braking system is started, the friction plate in the braking system clamps the brake disc to make the brake disc and the friction plate rub to achieve braking. After repeating the above process many times, cracks will appear in the dense area of ​​the brake disc. In the brake disc provided in the present application, after the cracks are generated, they will expand to the nanoporous area and along the interface of the cracked carbon / carbon particles in the nanoporous area. In the above process, the energy of the cracks is gradually absorbed by the nanoporous structure in the nanoporous area, so the cracks generated in the dense area will gradually disappear, so the toughness of the brake disc can be significantly improved and the service life of the brake disc can be extended.

[0034] It should also be noted that the above-mentioned nanoporous area and dense area are based on comparison at the nanoscale. There may be holes with a pore size of micrometer level in the dense area, which leads to the visual error of "the dense area looks looser than the nanoporous area" in the cross-sectional SEM photograph of the brake disc sample.

[0035] For example, the pore size of the nanoporous region may be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc. If the pore size of the nanoporous region is too small (less than 10 nm), the energy cannot be effectively absorbed during the crack propagation process, resulting in the fracture of the matrix; if the pore size of the nanoporous region is too large, the crack cannot be extended, resulting in the fracture of the dense region.

[0036] For example, the porosity of the nanoporous region may be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. If the porosity of the nanoporous region is too small, the loose area for absorbing crack energy is insufficient and the energy cannot be effectively absorbed; if the porosity of the nanoporous region is too large, the crack cannot be extended, causing the dense region to break.

[0037] In some embodiments of the present application, the size of the nanoporous region is in the range of 30 μm to 500 μm. It can be understood that the nanoporous region is a three-dimensional structure. The size of the nanoporous region is described by taking a disc-shaped brake disc as an example: the disc-shaped brake disc includes an upper surface, a lower surface, and a side surface connecting the upper and lower surfaces. The size of the nanoporous region in the cross section of the brake disc obtained by cutting the brake disc in any plane is in the range of 30 μm to 500 μm. Exemplarily, the size of the nanoporous area can be 30μm, 40μm, 50μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm, 200μm, 220μm, 250μm, 280μm, 300μm, 320μm, 350μm, 380μm, 400μm, 420μm, 450μm, 480μm, 490μm, 500μm, etc. By controlling the size of the nanoporous area within the above range, there can be a sufficiently large loose area on the nanoscale to absorb the energy of the crack to more fully improve the toughness of the brake disc, and the strength of the dense area will not be affected, thereby ensuring the braking effect of the brake disc while fully extending the service life of the brake disc.

[0038] In some embodiments of the present application, the total volume of the brake disc is used as a reference, and the sum of the volume percentages of the multiple nanoporous regions is within the range of 5% to 30%; that is, the sum of the volume percentages of all nanoporous regions in the brake disc is within the range of 5% to 30%. Exemplarily, the sum of the volume percentages of the nanoporous regions can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, etc. By controlling the sum of the volume percentages of the multiple nanoporous regions in the brake disc to be within the above range, there are a sufficient number of nanoporous regions spaced and dispersed in the dense region to absorb the energy of the dense regions at different positions that produce cracks when subjected to external force impact, so that the performance of each position of the brake disc is relatively uniform, so as to better and more comprehensively improve the toughness of the brake disc without affecting the wear resistance and strength of the brake disc.

[0039] In some embodiments of the present application, the nanoporous structure of the nanoporous region is formed by a plurality of stacked carbon particles and cracked carbon. Specifically, a plurality of carbon particles are stacked on each other, and it can be understood that gaps are formed between adjacent carbon particles, and the cracked carbon fills the gaps to form a continuous phase, thereby forming a nanoporous structure.

[0040] In some embodiments of the present application, the particle size of the carbon particles in the nanoporous region is 0.1 μm to 10 μm. In some specific embodiments, the D50 particle size of the carbon particles in the nanoporous region is 0.3 μm to 10 μm. Controlling the D50 particle size of the carbon particles within the above range is conducive to controlling the pore size of the nanoporous structure within a smaller range, which is more conducive to the absorption of crack energy. Exemplarily, the particle size of the carbon particles in the nanoporous region can be 0.3 μm, 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, etc.

[0041] In some embodiments of the present application, the material of the carbon particles in the nanoporous region includes but is not limited to at least one of microcrystalline carbon, graphite, coke and chopped carbon fibers. Among them, for the above-mentioned chopped carbon fibers, the above-mentioned particle size refers to the length of the chopped carbon fibers. In some specific embodiments, the length of the above-mentioned chopped carbon fibers is 14μm-60μm. Exemplarily, the length of the chopped carbon fibers can be 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, etc.

[0042] In some embodiments of the present application, the nanoporous region also includes silicon carbide particles; that is, the nanoporous region includes carbon particles, cracked carbon, and silicon carbide particles. In some specific embodiments, at this time, the carbon particles and silicon carbide particles in the nanoporous region are stacked with each other, and the cracked carbon fills the gaps formed by the stacking of the carbon particles and the silicon carbide particles to form a continuous phase, thereby forming a nanoporous structure. In this way, the nanoporous region can absorb the energy of the cracks in the dense region and improve the toughness of the brake disc.

[0043] In some embodiments of the present application, the D50 particle size of the silicon carbide particles in the nanoporous region is 0.3 μm to 20 μm. Controlling the D50 particle size of the silicon carbide particles within the above range is conducive to controlling the pore size of the nanoporous structure within a smaller range, which is more conducive to the absorption of crack energy. Exemplarily, the D50 particle size of the silicon carbide particles in the nanoporous region can be 0.3 μm, 0.5 μm, 1.0 μm, 2.0 μm, 5.0 μm, 8.0 μm, 10.0 μm, 12.0 μm, 15.0 μm, 18.0 μm, 20.0 μm, etc.

[0044] In some embodiments of the present application, based on the total mass of the nanoporous region, the nanoporous region includes 30% to 70% carbon particles, 10% to 40% cracked carbon, and 0 to 50% silicon carbide particles. Exemplarily, the mass percentage of carbon particles in the nanoporous region can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.; the mass percentage of cracked carbon in the nanoporous region can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. Exemplarily, the mass percentage of silicon carbide particles in the nanoporous region can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. In some specific embodiments, the nanoporous region includes 30% to 70% carbon particles, 10% to 40% cracked carbon, and 5% to 50% silicon carbide particles. Controlling the mass percentage of the above substances within the above range can not only ensure the pore size and porosity of the nanoporous structure of the nanoporous region, but also help to take into account the strength of the nanoporous region, thereby improving the toughness of the brake disc while ensuring the high strength of the brake disc.

[0045] In some embodiments of the present application, the length of the carbon fiber in the dense area is in the range of 1 cm to 2 cm. For example, the length of the carbon fiber in the dense area can be 1.0 cm, 1.1 cm, 1.2 cm, 1.3 cm, 1.4 cm, 1.5 cm, 1.6 cm, 1.7 cm, 1.8 cm, 1.9 cm, 2.0 cm, etc. In this way, the mechanical strength of the dense area can be ensured, thereby reducing the risk of cracks in the dense area, thereby helping to improve the braking effect of the brake disc and extend its service life.

[0046] In some embodiments of the present application, the edge region of the nanoporous region has a continuous phase of silicon carbide.

[0047] In some embodiments of the present application, the dense region also contains free silicon. Specifically, the silicon and silicon carbide in the dense region together form a continuous phase, and the carbon fibers are dispersed in the continuous phase as reinforcements.

[0048] In some embodiments of the present application, the porosity of the brake disc is in the range of 1%-5%. It is understandable that there may be micron-level pores in the dense area. Controlling the overall porosity of the brake disc within the above range is beneficial to the absorption of cracks in the dense area and to ensuring the mechanical properties of the dense area, thereby improving the performance of the final brake disc. Exemplarily, the porosity of the brake disc can be 1.00%, 1.20%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, 2.00%, 2.10%, 2.20%, 2.30%, 2.40%, 2.50%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc.

[0049] The present application also provides a method for preparing a brake disc, comprising the following steps:

[0050] S01, immersing the carbon fiber tow in a solution of the first resin, taking it out, drying, curing, and shearing it to obtain a carbon fiber reinforced resin strip;

[0051] S02, heat and pressurize the first raw material including carbon particles and the second resin powder in a mold to solidify, and then crush and sieve to obtain a granular second raw material; it can be understood that in the first raw material, the carbon particles are stacked on each other, and the second resin powder is filled in the gaps formed by the stacking of the carbon particles. In some embodiments of the present application, the carbon particles and the second resin powder are mixed in a solid phase mixing device. In some specific embodiments, the carbon particles and the second resin powder are mixed in a V-type mixer.

[0052] It should be noted that the above S01 and S02 are only distinguished in terms of steps, but not in terms of their order; in actual production, the carbon fiber reinforced resin strip can be prepared first, or the second raw material can be prepared first; or, the second raw material can be prepared first and then the carbon fiber reinforced resin strip; or, the carbon fiber reinforced resin strip and the second raw material can be prepared at the same time.

[0053] S03, mixing the carbon fiber reinforced resin strip, the second raw material, the third resin powder and the solvent, heating and stirring until the solvent evaporates to obtain a mixture; crushing and sieving the mixture, transferring it to a mold for heating and pressurizing and curing to obtain a brake disc blank; wherein the brake disc blank comprises a first material distribution area and a plurality of second material distribution areas dispersed in the first material distribution area, the first material distribution area comprises the carbon fiber reinforced resin strip and the third resin powder; the second material distribution area comprises the second raw material and the third resin powder;

[0054] S04. Carry out a carbonization treatment on the brake disc blank under a protective atmosphere, and then carry out a siliconizing treatment to obtain a brake disc; it should be noted that during the siliconizing treatment, based on the structural characteristics and raw material characteristics of the second material distribution area, it is difficult for silicon alone to penetrate into the second material distribution area. Among them, the carbonization treatment can convert the first resin, the second resin powder and the third resin powder into cracked carbon; the siliconizing treatment can cause the cracked carbon in the first material distribution area to react with silicon and transform into silicon carbide. In some embodiments, there may be silicon alone impregnated into the raw materials at the edge of the second material distribution area, which will result in the presence of silicon carbide and / or silicon alone on the edge of the nanoporous area in the final brake disc.

[0055] The brake disc includes a dense area and a plurality of nanoporous areas spaced apart in the dense area; the dense area includes carbon fiber reinforced silicon carbide material, and the nanoporous area includes cracked carbon in a continuous phase and carbon particles dispersed in the cracked carbon; the pore size of the nanoporous area is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%.

[0056] In some embodiments of the present application, the first resin, the second resin powder, and the third resin powder include but are not limited to phenolic resin. Further, in some specific embodiments, the first resin, the second resin powder, and the third resin powder are selected from thermoplastic phenolic resin.

[0057] In some embodiments of the present application, in step S01, the solid content of the first resin solution is 40% to 60%. In some specific embodiments, the first resin solution is a phenolic resin solution with a solid content of 40% to 60%.

[0058] In some embodiments of the present application, in step S01, the carbon fiber tow impregnated with the solution of the first resin is dried at 50°C to 80°C, then placed at 130°C to 160°C for curing, and then cut into carbon fiber reinforced resin strips with a length of 0.5cm to 3cm. Exemplarily, the drying temperature may be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc. Exemplarily, the curing temperature may be 130°C, 140°C, 150°C, 160°C, etc. Exemplarily, the length of the carbon fiber reinforced resin strip may be 0.5cm, 1.0cm, 1.5cm, 2.0cm, 2.5cm, 3.0cm, etc. Controlling the length of the carbon fiber reinforced resin strip within the above range is conducive to the mixing of the carbon fiber reinforced resin strip, the second raw material and the third resin powder.

[0059] In some embodiments of the present application, in step S02, based on the total mass of the first raw material, the first raw material includes 30% to 60% of the carbon particles, 20% to 50% of the second resin powder and 0% to 40% of silicon carbide particles. Exemplarily, the mass content of carbon particles in the first raw material can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. Exemplarily, the mass content of the second resin powder in the first raw material can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. In some specific embodiments, the first raw material also includes silicon carbide particles. At this time, based on the total mass of the first raw material, the first raw material includes 30% to 60% of the carbon particles, 20% to 50% of the second resin powder and 10% to 40% of silicon carbide particles. For example, the mass percentage of silicon carbide particles in the first raw material can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. By controlling the content of the above substances within the above range, the toughness and strength in the nanoporous region of the brake disc can be adjusted to be more appropriate, and a higher dynamic friction coefficient can be achieved, thereby adjusting the performance of the final brake disc to be better.

[0060] In some embodiments of the present application, in step S02, the first raw material is pressurized and cured at 130° C. to 160° C. to obtain a block of the first raw material. For example, the pressurized curing temperature may be 130° C., 135° C., 140° C., 145° C., 150° C., 155° C., 160° C., etc.

[0061] In some embodiments of the present application, in step S02, after the block-shaped first raw material is crushed, it is sieved with a 50-400 mesh screen. Exemplarily, the mesh number of the screen can be 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, 350, 380, 400, etc. Controlling the mesh number of the screen within the above range is conducive to the mixing of the second raw material with the carbon fiber reinforced resin strip and the third resin powder, and then it is conducive to regulating the distribution of the subsequent first material distribution area and the second material distribution area, and then it is conducive to regulating the parameters of the final nanoporous area.

[0062] In some embodiments of the present application, in step S03, the second raw material, the carbon fiber reinforced resin strip, the third resin powder and the solvent are mixed and heated and stirred to completely volatilize the solvent; wherein the temperature of heating and stirring is 50°C to 70°C. Exemplarily, the temperature of the heating and stirring can be 50°C, 55°C, 60°C, 65°C, 70°C, etc. In some embodiments of the present application, the solvent includes but is not limited to alcohol.

[0063] In some embodiments of the present application, in step S03, based on the total mass of the mixture, the mixture includes 20% to 50% of the carbon fiber reinforced resin strip, 20% to 40% of the second raw material and 20% to 40% of the third resin powder. Exemplarily, the mass content of the carbon fiber reinforced resin strip in the mixture can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. Exemplarily, the mass content of the second raw material in the mixture can be 20%, 25%, 30%, 35%, 40%, etc. Exemplarily, the mass content of the third resin powder in the mixture can be 20%, 25%, 30%, 35%, 40%, etc. By controlling the mass content of the carbon fiber reinforced resin strip, the second raw material and the third resin powder within the above range, the proportion of the nanoporous area in the brake disc can be controlled to be appropriate, so that the brake disc has both good toughness and good strength, so that the final brake disc has both good braking effect and long service life.

[0064] In some embodiments of the present application, in step S03, the mixed material is crushed and then sieved with a 15-30 mesh screen. In this way, the particle size of the material can be controlled within a suitable range, and then the size of the second material partition in the brake disc blank can be controlled within a suitable range. On the basis of successfully manufacturing the brake disc provided by the present application, the size of the nanoporous area can be further controlled within a more suitable range to ensure that the comprehensive performance of the brake disc is better.

[0065] In some embodiments of the present application, in step S04, the brake disc blank is kept at a holding temperature of 800°C to 1200°C for 2h to 6h under a protective atmosphere. For example, the holding temperature may be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1050°C, 1200°C, etc. For example, the holding time may be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, etc.

[0066] In some implementations of the present application, in step S04, the siliconizing treatment may be a liquid phase siliconizing treatment of the brake disc blank.

[0067] In some embodiments of the present application, in step S04, after the siliconizing treatment, the brake disc is further subjected to post-processing to obtain a brake disc that meets actual use requirements. The post-processing process includes flat grinding the surface of the brake disc.

[0068] The embodiment of the present application also provides a braking system, including the brake disc provided in the embodiment of the present application. Due to the use of the carbon-ceramic brake disc provided in the present application, the braking system has a better braking effect, higher reliability, and longer service life.

[0069] In some embodiments of the present application, the braking system includes a carbon-ceramic brake disc, a brake caliper bracket, a brake caliper housing, and a friction plate.

[0070] The embodiment of the present application provides a vehicle, including the braking system provided by the present application. Due to the braking system provided by the present application, the vehicle has good market competitiveness.

[0071] In some embodiments of the present application, the means of transportation include vehicles and airplanes; wherein the vehicles include automobiles and trains for rail transit.

[0072] The technical solution of the present application is further described in detail below with multiple embodiments.

[0073] Example 1

[0074] (1) A 12K carbon fiber tow is immersed in a solution of a first resin (specifically a phenolic resin) having a solid content of 50%, taken out and dried at 80°C, and cured in an environment of 150°C, and then cut into carbon fiber reinforced resin strips with a length of 2 cm.

[0075] (2) uniformly mixing carbon particles (specifically graphite) with a particle size of 50:50 in a mass ratio and a second resin powder (specifically phenolic resin) in a V-type mixer to obtain a first raw material; transferring the first raw material to a mold and pressurizing and curing it at 150° C. to obtain a block of the first raw material, which is then crushed and sieved with a 100-mesh sieve to obtain a second raw material.

[0076] (3) Dispersing the carbon fiber reinforced resin strip, the second raw material and the third resin powder in a mass ratio of 40:30:30 in a solvent (specifically alcohol) and heating and stirring at 60° C. for 1 hour to completely evaporate the solvent to obtain a mixture; crushing the mixture, sieving it with a 20-mesh membrane screen, and then transferring it to a mold and pressurizing and curing it at 150° C. to obtain a brake disc blank.

[0077] (4) The brake disc blank is kept at 1000° C. for 4 hours in a nitrogen atmosphere, and then the carbonized brake disc blank is subjected to liquid phase siliconization, and finally surface processing is performed to obtain a brake disc. The brake disc includes a dense area and a plurality of nanoporous areas dispersed in the dense area.

[0078] Example 2

[0079] The difference from Example 1 is that in step (2), the first raw material includes carbon particles, second resin powder and silicon carbide particles in a mass ratio of 30:50:20, wherein the particle size of the silicon carbide particles is 0.5 μm.

[0080] Example 3

[0081] The difference from Example 2 is that in step (2), the first raw material includes carbon particles, second resin powder and silicon carbide particles in a mass ratio of 60:20:20.

[0082] Example 4

[0083] The difference from Example 2 is that in step (2), the first raw material includes carbon particles, second resin powder and silicon carbide particles in a mass ratio of 30:50:20.

[0084] Example 5

[0085] The difference from Example 2 is that in step (2), the first raw material includes carbon particles and the second resin powder in a mass ratio of 80:20.

[0086] Example 6

[0087] The difference from Example 2 is that in step (2), the first raw material includes carbon particles and the second resin powder in a mass ratio of 20:80.

[0088] Example 7

[0089] The difference from Example 2 is that in step (3), the mixture includes carbon fiber reinforced resin strips, the second raw material and the third resin powder in a mass ratio of 20:40:40.

[0090] Example 8

[0091] The difference from Example 2 is that in step (3), the mixture includes carbon fiber reinforced resin strips, the second raw material and the third resin powder in a mass ratio of 50:20:30.

[0092] Example 9

[0093] The difference from Example 2 is that in step (3), the mixture includes carbon fiber reinforced resin strips, the second raw material and the third resin powder in a mass ratio of 60:10:40.

[0094] Example 10

[0095] The difference from Example 2 is that in step (3), the mixture includes carbon fiber reinforced resin strips, the second raw material and the third resin powder in a mass ratio of 10:50:40.

[0096] Embodiment 11

[0097] The difference from Example 2 is that in step (3), after the block-shaped first raw material is crushed, it is sieved using a 500-mesh sieve; in step (3), the crushed mixture is sieved using a 50-mesh sieve.

[0098] Example 12

[0099] The difference from Example 2 is that in step (3), after the block-shaped first raw material is crushed, it is sieved with a 30-mesh sieve; in step (3), the crushed mixture is sieved with a 10-mesh sieve.

[0100] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0101] Comparative Example 1

[0102] (1) 2 cm long 12K short chopped carbon fibers are mixed evenly with phenolic resin powder, carbon powder, and silicon carbide powder, and then placed in a mold for pressurized curing to obtain a molded blank, wherein the mass ratio of carbon fiber: phenolic resin: carbon powder: silicon carbide powder is 40:45:9:6.

[0103] (2) The molded body is carbonized at a temperature of 1000°C for 4 hours in a nitrogen atmosphere.

[0104] (3) The carbonized body is subjected to liquid phase siliconization and processing to obtain a brake disc.

[0105] Performance Testing

[0106] (1) The brake disc sample was pretreated to expose its cross section, and the pore size of the nanoporous region of the brake disc was measured by SEM; the SEM photo of a cross section of the brake disc in Example 2 is shown in FIG. Figure 2 As shown;

[0107] (2) Determine the density and porosity of the brake disc according to the provisions of GB / T 1966;

[0108] (3) Determine the bending strength of the brake disc in accordance with the provisions of GB / T 6569;

[0109] (4) Determine the interlaminar shear strength of the brake disc in accordance with ASTM D2344 / D2344M-13;

[0110] (5) Determine the compressive strength of the brake disc in accordance with the provisions of GB / T 34559;

[0111] (6) Determine the impact toughness of the brake disc in accordance with the provisions of GB / T 14389;

[0112] (7) Use TC-3000 thermal constant tester to test the thermal conductivity of the brake disc according to GJB1201.1-91;

[0113] (8) The dynamic friction coefficient of the brake disc is tested using an MM-1000 friction tester. The effective friction surface of the test ring has an outer diameter of D75mm / inner diameter of D55mm×10mm, and a specific pressure of 98N / cm 2 , inertia is 3kgf·cm·s 2 , linear speed is 25m / s.

[0114] Table 1

[0115]

[0116] Table 2

[0117]

[0118] It can be seen from the parameters in Table 1 and Table 2 that the impact toughness and bending strength of the brake disc provided in the embodiment of the present application are significantly higher than those of the comparative brake disc, and the parameters such as the compressive strength, shear strength, thermal conductivity and dynamic friction coefficient of the brake disc provided in the embodiment also meet the use requirements.

[0119] In addition, by comparing the data between Example 1 and Example 5, it can be found that when the mass ratio of the carbon powder to the second resin powder in the first raw material is within the range further suggested in this application, the performance of the brake disc obtained is better. By comparing the data of Example 1 and Examples 2-4, it is not difficult to see that when the first raw material also contains silicon carbide and the content of each raw material is within the range further suggested in this application, the mechanical strength and dynamic friction coefficient of the brake disc are better. By comparing the data of Examples 7-8 and Examples 9-10, it can be found that when the content of each substance in the second raw material is within the range further suggested in this application, the overall performance of the brake disc is better. By comparing the data of Example 2 with that of Examples 11-12, it is not difficult to find that the mesh size of the first raw material and the second raw material after crushing will also affect the performance of the final brake disc. When the mesh size of the crushing and sieving of the two meets the parameters further suggested in the examples of this application, it is easier to obtain a brake disc with balanced performance and better performance.

[0120] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A brake disc, characterized in that: comprising a dense region and a plurality of nanoporous regions spaced apart and distributed in the dense region; The dense region includes carbon fiber reinforced silicon carbide material, and the nanoporous region includes cracked carbon in a continuous phase and carbon particles distributed in the cracked carbon; the pore size of the nanoporous region is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%.

2. The brake disc according to claim 1, characterized in that: The size of the nanoporous region is in the range of 30 μm to 500 μm.

3. The brake disc according to claim 1, characterized in that: Based on the volume of the brake disc, the sum of the volume percentages of the plurality of nanoporous regions is in the range of 5% to 30%.

4. The brake disc according to any one of claims 1 to 3, characterized in that: Based on the total mass of the nanoporous region, the nanoporous region includes 30% to 70% of the carbon particles, 10% to 40% of the cracked carbon, and 0% to 50% of the silicon carbide particles.

5. The brake disc according to claim 4, characterized in that In the nanoporous region, the mass percentage of the silicon carbide particles is 5% to 50%.

6. The brake disc according to claim 1, characterized in that The particle size of the carbon particles is 0.1 μm to 10 μm.

7. The brake disc according to claim 4, characterized in that The D50 particle size of the silicon carbide particles is 0.3 μm to 20 μm.

8. A method for preparing a brake disc, characterized in that: The following steps are involved: (1) immersing a carbon fiber tow into a solution of a first resin, taking it out, drying, curing, and shearing it to obtain a carbon fiber reinforced resin strip; (2) heating and pressurizing a first raw material including carbon particles and a second resin powder in a mold to solidify the first raw material, and then crushing and sieving the first raw material to obtain a granular second raw material; (3) Mixing the carbon fiber reinforced resin strip, the second raw material, the third resin powder and the solvent, heating and stirring until the solvent evaporates to obtain a mixture; crushing and sieving the mixture, transferring it to a mold for heating and pressurizing to cure, and obtaining a brake disc blank; wherein the brake disc blank comprises a first material distribution area and a plurality of second material distribution areas dispersed in the first material distribution area, the first material distribution area comprising the carbon fiber reinforced resin strip and the third resin powder; the second material distribution area comprising the second raw material and the third resin powder; (4) performing a carbonization treatment on the brake disc blank under a protective atmosphere; and then performing a siliconizing treatment to obtain a brake disc; Wherein, the brake disc includes a dense area and a plurality of nanoporous areas spaced apart in the dense area; the dense area includes carbon fiber reinforced silicon carbide material, and the nanoporous area includes cracked carbon in a continuous phase and the carbon particles dispersed in the cracked carbon; wherein, the pore size of the nanoporous area is in the range of 10nm to 100nm, and the porosity is in the range of 15% to 30%.

9. The preparation method according to claim 8, characterized in that: Based on the total mass of the mixture, the mixture includes 20% to 50% of the carbon fiber reinforced resin strip, 20% to 40% of the second raw material and 20% to 40% of the third resin powder; The length of the carbon fiber reinforced resin strip is 0.5 cm to 3 cm.

10. The preparation method according to claim 8, characterized in that: Based on the total mass of the first raw material, the first raw material includes 30% to 60% of the carbon particles, 20% to 50% of the second resin powder, and 0% to 40% of silicon carbide particles.

11. The preparation method according to claim 8, characterized in that: In step (2), the sieving is performed using a sieve of 50 to 400 meshes; in step (3), the sieving is performed using a sieve of 15 to 30 meshes.

12. A braking system, characterized in that: The brake system comprises a brake disc as claimed in any one of claims 1 to 7.

13. A means of transport, characterized in that: The vehicle comprises a braking system as claimed in claim 12.

Citation Information

Cited By

  • Brake disc and preparation method, brake system, and vehicle

    EP4768462A1

  • Brake disc and preparation method, brake system, and vehicle

    WO2025039503A1